Effects of different irrigation frequencies and incorporation of rice straw on yield and water productivity of wheat crop - Tunio, Mazhar Hussian; Gao, Jianmin; Talpur, Mashooque Ali; Lakhiar, Imran Ali; Chandio, Farman Ali; Shaikh, Sher Ali; Solangi, Kashif Ali (International Journal of Agricultural and Biological Engineering, 2020)
The current rapid increase in irrigation water consumption is considered unsustainable and threatens the world food production. Therefore, it is mandatory to promote modern techniques and to manage existing conventional irrigation methods. The present study was attempted to determine the effects of different irrigation frequencies and rice straw incorporation rates on yield and water productivity of the wheat crop. The experiment was arranged with randomize complete block design involving nine treatments (RS0I7, RS0I15, RS0I22, RS1I7, RS1I15, RS1I22, RS2I7, RS2I15 and RS2I22) under three replications. Results exposed that the incorporation of rice straw with different irrigation frequencies significantly improved physico-chemical properties of soil. Moreover, soil bulk density, infiltration rate, pH, electrical conductivity significantly decreased and soil porosity significantly increased under all treatments. Furthermore, maximum crop yield and crop water productivity of 7706.4 kg/hm2 and 1.92 kg/m3 respectively were found under RS1I15 treatment. Based on experimental results it can be concluded that irrigation frequency and incorporation of rice straw had significant effects on the physico-chemical properties of soil, total grain yield and water productivity of the wheat crop. However, this study suggested that the wheat crop yield and water productivity could be increased by incorporating 1 t/hm2 rice straw with 15 d of irrigation frequency. Keywords: physico-chemical, irrigation frequency, rice straw, wheat, crop water productivity DOI: 10.25165/j.ijabe.20201301.4790 Citation: Tunio M H, Gao J M, Talpur M A, Lakhiar I A, Chandio F A, Shaikh S A, et al. Effects of different irrigation frequencies and incorporation of rice straw on yield and water productivity of wheat crop. Int J Agric & Biol Eng, 2020; 13(1): 138–145.